Cross-Border Onomastic Systems of Western Ukraine and Eastern Poland: Synchronic and Diachronic Aspects. - Redkva, Yaroslav; Lukashchuk, Michael (My University, 2023)
The paper presents a comparative synchronic and diachronic study of two cross-border oikonymic systems of western Ukraine and eastern Poland. We analyse the structure and semantics of Ukrainian and Polish oikonyms. The paper traces the evolution between two cross-border oikonymic systems on the structural and derivational levels. As a basis for structural and derivational comparison we put forward the idea of invariantness. A number of structural models are used for derivational level. We conduct an analysis of the semantics of words comprising the basis for place names that enables us to trace the development of semantic structures. The paper focuses on structural and lexical-semantic aspects that are of intralingual character; social, functional, psychological, and cognitive aspects aim at creating an ontological picture of analysed oikonymy as a social phenomenon. We study the problem of oikonym motivation in Polish and Ukrainian linguistic environments. The onomastic parallelism of Slavic cross-border oikonymic systems is a crucial new aspect of studies and plays an important role for theoretical onomastics. It also is a new approach for historical theoretical onomastics; principles of nomination production are a keystone for applied onomastics.
Keywords: place names, cross-border oikonymic systems, Ukrainian and Polish oikonyms, comparative studies, motivation of oikonyms